Pengembangan Mobile-Learning SARITHA-Apps Untuk Meningkatkan Hasil Belajar Dan Berpikir Kritis Mahasiswa S1 Pendidikan Biologi Universitas Palangka Raya - Elda Susanti E. B. Dopo; Agus Haryono; Saritha Kittie Uda; Aditama Kittie Aidon Uda (FKIP Universitas Palangka Raya, 2024)
This research aims to develop mobile-learning SARITHA-Apps, describe product validity, analyze the development of mobile-learning SARITHA-Apps towards improving learning outcomes and critical thinking of undergraduate students in the Biology Education Study Program, FKIP Palangka Raya University. This research refers to the ADDIE development design and data collection using questionnaire sheets, media expert assessment sheets and material expert assessment sheets. The research results show: (1) one product has been produced as a result of the development of Mobile-Learning Environmental Science material, namely the SARITHA-Apps Mobile-Learning Application; (2) The average result of the Expert Team's assessment of the suitability of the SARITHA-Apps Mobile-Learning Application instrument and product is 91%, which means it is in the